Effect of Copper Applications to Soil on Growth and Mineral Contents of Tomato Plants - SONMEZ, SAHRIYE (Asian Journal of Chemistry, 2010)
Copper-containing fertilizers, fungicides and bactericides are extensively used to control plant diseases in greenhouses in Turkey. Excessive applications of these materials have led to the accumulation of potentially toxic elements and imbalance the mineral nutrition of plants. The objective of this study was to evaluate the effects of Cu applications to soil on growth and mineral contents in different organs of tomato plants grown in greenhouse. For this purpose, tomato seedlings were grown for 10 weeks in a computer-controlled greenhouse and range of Cu was applied to soil as CuSO4.5H2O (0, 250, 500, 1000 and 2000 mg kg-1). The results showed that the leaf, stem and root biomass decreased with increasing Cu supply to soil. The N, Mn and Cu contents of plant tissues increased with increasing Cu supply to soil, whereas the P, K, Ca and Fe contents of plant tissues decreased. The Mg content of stem decreased with increasing Cu supply to soil while leaf and root Mg content were not affected by these treatments. The Zn contents of leaf and root decreased with increasing Cu supply to soil but not in the stem. Increasing Cu supply to soil caused a decrease in root growth, reducing uptake nutrient elements such as P, K, Ca, Mg, Fe and Zn. As a result, increasing Cu supply to soil could imbalance the mineral nutrition and inhibit the growth of tomato plants. Therefore, caution should be taken when applying copper in soil.